Fusion Integration: COM Trajectory From a Force Platform - Brodie, M.; Walmsley, A.; Page, W. (Journal of Applied Biomechanics, 2007)
A fusion integration algorithm is used to estimate the one-dimensional center of mass (COM) trajectory from force platform data.